Kontrola siły roboczej w gospodarce kolonialnej Ameryki hiszpańskiej: encomienda, repartimiento i niewolnictwo - Kubiaczyk, Filip (Studia Europaea Gnesnensia, 2011)
The aim of the article is to demonstrate how the system of forced labour developed within the Spanish colonial economy, a system that served what is termed workforce control. In this context, I analyse the structure of pre-Hispanic societies of America and the mental type of the Spanish colonizer, which had a significant impact on the shape of the colonial labour system. Next, I present how the institutions of encomienda, repartimiento and slavery functioned in practice in the main areas of the colonial economy.